2016
DOI: 10.3892/mmr.2016.5969
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative activity of epigallocatechin-3-gallate and silibinin on soft tissue sarcoma cells

Abstract: Disseminated soft tissue sarcomas (STS) present a therapeutic dilemma. The first-line cytostatic doxorubicin demonstrates a response rate of 30% and is not suitable for elderly patients with underlying cardiac disease, due to its cardiotoxicity. Well-tolerated alternative treatment options, particularly in palliative situations, are rare. Therefore, the present study assessed the anti-proliferative effects of the natural compounds epigallocatechin-3-gallate (EGCG), silibinin and noscapine on STS cells. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Furthermore, it stabilizes cellular membranes and regulates membrane permeability that inhibits toxins entry into liver cells. Silymarin inhibits fibrogenesis in the liver by inhibition of stellate cell proliferation and its further transformation into myofibroblasts [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it stabilizes cellular membranes and regulates membrane permeability that inhibits toxins entry into liver cells. Silymarin inhibits fibrogenesis in the liver by inhibition of stellate cell proliferation and its further transformation into myofibroblasts [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…2), one of the flavonoids isolated from Silybum marianum L. Gaertn, is commonly exploited for the treatment hepatic diseases in China, Germany and Japan. In addition, silibinin is also found to display various biological activities including anti-oxidative, anti-proliferative, anti-bacterial, anti-fungal, neuro-protective, anti-leishmanial, anti-osteoclastic and anti-metastatic activities [310][311][312][313][314][315][316][317]. Previous studies have reported that silibinin exerts remarkable effects in numerous cancers such as renal, hepatocellular and pancreatic carcinoma, bladder, breast, colorectal, ovarian, lung, salivary gland, prostate and gastric cancers, through the induction of apoptosis, inhibition of tumor growth, metastasis and angiogenesis [318][319][320][321][322][323][324][325][326][327][328].…”
Section: Silibininmentioning
confidence: 99%
“…Harati et al. () assessed the antiproliferative effects of noscapine on human soft tissue sarcomas (STS) cells. Noscapine exhibited cytostatic effects on STS cells, as assessed using the bromodeoxyuridine (BrdU) and 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT) cell proliferation assays at 24 h; however, these effects could not be validated by real‐time cell analysis over a longer time period.…”
Section: Assessmentmentioning
confidence: 99%